Discotic columnar liquid-crystalline polymer semiconducting materials with high charge-carrier mobility via rational macromolecular engineering. Issue 21 (5th May 2017) - Mu, Bin; Hao, Xingtian; Chen, Jian; Li, Qian; Zhang, Chunxiu; Chen, Dongzhong
Abstract : Well-prepared side-chain discotic liquid crystal polymers with shorter spacers in ordered columnar phases are fascinating and promising cost-effective, solution-processable organic semiconducting materials for various potential optoelectronic device applications. Abstract : Discotic liquid crystal (DLC) polymers in columnar phases are fascinating and promising organic semiconducting materials as they combine the advantages of DLCs with the flexibility and good processability of polymers. Synthetic challenges hinder progress in this area, particularly in the preparation of such polymers in a well-controlled way. A group of butoxy-substituted triphenylene (TP)-based side-chain DLC polymers have been prepared by reversible addition fragmentation chain transfer (RAFT) polymerization via rational macromolecular engineering with particular emphasis on the effects of spacer length and molecular weight. The DLC polymers with shorter alkyl spacers exhibit various ordered columnar LC or columnar plastic phases and easily realize macroscopic homeotropic or planar columnar alignments. Very high hole mobilities over 0.1 cm 2 V −1 s −1 are achieved by the well-defined, high-molecular-weight side-chain DLC polymers with shorter spacers, as evaluated by time-of-flight measurements. These high hole mobilities are mainly attributed to positive coupling between the side-chain TP discogens and the polymer backbones. These DLC polymers and the applied macromolecular engineering principles may pave the way for cost-effective, solution-processable organic semiconducting materials for various electronic and optoelectronic device applications.